Asuhan Kebidanan Continuity Of Care (COC) Pada Ibu Hamil, Bersalin, Nifas, Bayi Baru Lahir dengan Asfiksia, Keluarga Berencana Pada Ny. S Di BPM Nurhaida Tarigan Kecamatan Gebang Kab Langkat Provinsi Sumatera Utara - Talita, Dina Warmi; Eliana Br Bangun; Nuriyunita; Marlina, Desi; Ayu Ara; Hutabarat, Dewi Sartika; Srininta (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2021)
810 women die due to pregnancy and childbirth. Between 2000 and 2017, the maternal mortality ratio (MMR, 305 maternal deaths per 100,000 live births) fell by about 38% worldwide, 94% of all maternal deaths occurring in low- and middle-income countries. Comprehensive midwifery care (Continuity of Care/CoC) can optimize detection of high-risk maternal and neonatal. Purpose: this study was to conduct Midwifery Care for Pregnant, Maternity, BBL, Postpartum and Family Planning Mothers at Mrs S at BPM Nurhaida Tarigan in 2022. Method: This research is a descriptive type of research with a case study approach. In this case study, the author takes the subject of NY.S GIIPIA0 25 years old to family planning acceptors at Bpm Nurhaida Tarigan. Maternity care for NY.S starts from the first contact for a pregnancy checkup on September 5, 2020 until the end of the postpartum period and becomes an acceptor for family planning (KB) on April 15, 2022 in accordance with pregnancy care standards. Result: On examination, it was found that the mother in the first trimester experienced nausea, vomiting and dizziness, in the second trimester pain in the waist and in the third trimester she often urinated. Suggest: to Mrs. S to ask more questions to health services or to make more use of existing facilities as input to receive information about prevention and treatment in particular for pregnant women, maternity, postpartum, BBL and family planning.